Peran penyerapan tenaga kerja, ekspor, dan pendidikan dalam pertumbuhan ekonomi di Jawa Tengah - Ayudita, Salma Fitri; Purnomo, Didit (Journal of Economics Research and Policy Studies, 2024)
This study examines the impact of labour absorption, exports, and education on economic growth in Central Java. Utilizing panel data regression analysis with data from 35 districts/towns in Central Java from 2020-2022. The findings show that all three variables have a positive and beneficial impact on economic growth. Labour absorption and improvements in education quality play an important role in driving productivity, while exports contribute to increasing foreign exchange and market expansion. These findings emphasize the importance of policies focused on human resource development, enhancing export competitiveness, and equalizing access to education to support sustainable economic growth in Central Java.